Extensive Uncharted Biodiversity: The Parasite Dimension. (18th September 2018) - Okamura, Beth; Hartigan, Ashlie; Naldoni, Juliana
Abstract: Parasites are often hidden in their hosts and exhibit patchy spatial distributions. This makes them relatively difficult to detect and sample. Consequently we have poor knowledge of parasite diversities, distributions, and extinction. We evaluate our general understanding of parasite diversity and highlight the enormous bias in research on parasites such as helminths and arthropods that infect vertebrate hosts. We then focus on Myxozoa as an exemplary case for demonstrating uncharted parasite diversity. Myxozoans are a poorly recognized but speciose clade of endoparasitic cnidarians with complex life cycles that have radiated to exploit freshwater, marine, and terrestrial hosts by adopting strategies convergent to those of parasitic protists. Myxozoans are estimated to represent some 20% of described cnidarian species—greatly outnumbering the combined species richness of scyphozoans, cubozoans, and staurozoans. We summarize limited understanding of myxozoan diversification and geographical distributions, and highlight gaps in knowledge and approaches for measuring myxozoan diversity. We close by reviewing methods and problems in estimating parasite extinction and concerns about extinction risks in view of the fundamental roles parasites play in ecosystem dynamics and in driving host evolutionary trajectories.